Программная реализация метода оценки риска от загрязнения атмосферного воздуха выбросами химического производства - Кожевникова, М. Ф.; Левенец, В. В.; Ролик, И. Л. (НТУ "ХПИ", 2009)
Розроблено програму EсoAіr, що реалізує методологію оцінки ризику. В основі методики лежить оцінка впливу на здоров'я людини речовин, що перебувають в атмосферному повітрі. Представлено результати застосування програми EсoAіr. Зроблено висновки про функціональні можливості програми й перспективи її розвитку.

The EсoAіr program realizing methodology of risk evaluation is developed. The estimate of exposure on public health of the substances which are being in atmospheric air forms a basis of the method. Results of application of EсoAir program are presented. Resumes about functional capabilities of the program and perspectives of its development are made.
Keywords: идентификация опасности; оценка зависимости; оценка воздействия; характеристика риска; программа EсoAir